Perspectives of overweight children regarding sports (Research, Society and Development, 2022)
Considering the growing framework of childhood obesity in all of the world and the importance of a physically active lifestyle, health promotion strategies that take into account the listening of those involved may collaborate to the actions of interventions being more accepted by the communities. The aim of this study was to identify the experiences and expectations of overweight children living in social vulnerability situation about the practice of sports before the beginning of an intervention project which had as objective investigating the effects of a multicomponent intervention on health markers of overweight children. With a qualitative approach, this study is part of the macro-project called SHOW – Sport and Health for Overweight children. Overweight children aged 8 to 12 years old participated in this investigation. To collect the information, a group interview was developed through games. The investigative dynamics were recorded in audio and video, being later transcribed, giving rise to the corpus of analysis. Among the main findings, the expanded perception of sport was identified; the positive expectation in learning sport; reports of negative sporting experiences throughout life. The children's perception was essential for the discussion and the building of the sports intervention plan developed for the SHOW project.